Communication in struggle: the role of educators and scientists - A. Lapa; N.D.L. Pretto (Universitat Politècnica de València, 2019)
This paper analyses on the integration of ICT in education as a space for citizenship education in digital culture. This integration presents a special opportunity to promote a re-signification of the role of educational institutions in the required paradigm shift in education. The founding principles of the new paradigm are presented through the description and analysis of the challenges posed to educators and scientists who should  effectively assume the role of knowledge and culture producers that incorporates the communicative dimension of modern society. Among the challenges, we examine the reach of digital presence as long as the universality is a goal not yet achieved, and the appropriation of digital communication stands on large corporations with global capital concentration. Therefore, severe restrictions on democracy and neutrality issues arise, both in mass media as well as in digital networks, as exposed by the new modes of social manipulation through controlled algorithms designed by these corporations. For this reason, a strong articulation between education and communication is required which should be part of the university revitalization, as a path committed to the education of citizens for social emancipation. The proposal presented is based on the defense of public intellectuals who assume a communicative and political stance which embrace the hacker culture. That means to explore alternatives in the hegemonic structure as much as to construct networks for dissemination of information for collaborative learning which is open and engaged with social transformation.